The Role of Cardiovascular Magnetic Resonance Imaging in the Assessment of Myocardial Fibrosis in Young and Veteran Athletes: Insights From a Meta-Analysis - Androulakis, Emmanuel; Mouselimis, Dimitrios; Tsarouchas, Anastasios; Antonopoulos, Alexios; Bakogiannis, Constantinos; Papagkikas, Panagiotis; Vlachopoulos, Charalambos (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac magnetic resonance (CMR) combined with late gadolinium enhancement (LGE) has revealed a non-negligible increased incidence of myocardial fibrosis (MF) in athletes compared to healthy sedentary controls. Objective: The aim of this systematic research and meta-analysis is to investigate and present our perspective regarding CMR indices in athletes compared to sedentary controls, including T1 values, myocardial extracellular volume (ECV) and positive LGE indicative of non-specific fibrosis, also to discuss the differences between young and veteran athletes. Methods: The protocol included searching, up to October 2021, of MEDLINE, EMBASE, SPORTDiscus, Web of Science and Cochrane databases for original studies assessing fibrosis via CMR in athletes. A mean age of 40 years differentiated studies' athletic populations to veteran and young. Results: The research yielded 14 studies including in total 1,312 individuals. There was a statistically significant difference in LGE fibrosis between the 118/759 athletes and 16/553 controls (Z = 5.2, P < 0.001, I2 = 0%, PI = 0.45). Notably, LGE fibrosis differed significantly between 546 (14.6%) veteran and 140 (25.7%) young athletes (P = 0.002). At 1.5T, T1 values differed between 117 athletes and 48 controls (P < 0.0001). A statistically significant difference was also shown at 3T (110 athletes vs. 41 controls, P = 0.0004), as well as when pooling both 1.5T and 3T populations (P < 0.00001). Mean ECV showed no statistically significant difference between these groups. Conclusions: Based on currently available data, we reported that overall LGE based non-specific fibrosis and T1 values differ between athletes and sedentary controls, in contrast to ECV values. Age of athletes seems to have impact on the incidence of MF. Future prospective studies should focus on the investigation of the underlying pathophysiological mechanisms.